Leading with Ethics and Values: Exploring the Impact on Social Innovation in the Public Sector - Hong Tran, Kiet; Nguyen, Kim Van; Ly, Thoa Thyen (Aurora: Journal of Emerging Business Paradigms, 2025)
This study explores the role of ethical and values-based leadership in fostering social innovation in the public sector of Vietnam. With a growing need for innovative approaches to address complex societal challenges, the research examines how ethical leadership practices shape organizational cultures that promote innovation. Through qualitative interviews with public leaders, the study identifies three key themes: (1) moral framing of innovation as a social responsibility, (2) the creation of an empowering organizational culture that fosters psychological safety for employees, and (3) the exercise of ethical judgment to navigate institutional tensions and foster change. The findings reveal that leaders who prioritize ethics and values can create an environment where innovation thrives, even in the face of bureaucratic resistance and political constraints. This study contributes to the theoretical understanding of ethical leadership in the public sector and provides practical insights for public administrators aiming to drive social innovation. The research also highlights the importance of aligning innovation efforts with core societal values, fostering an inclusive environment that encourages risk-taking, and applying moral decision-making to overcome institutional barriers. The novel contribution of this study lies in its contextual focus on Vietnam, providing valuable insights into how public sector leaders in emerging economies can integrate ethics into their leadership practices to enhance social innovation.